2011
DOI: 10.1007/s00284-011-9956-7
|View full text |Cite
|
Sign up to set email alerts
|

The Green Microalga Chlorella saccharophila as a Suitable Source of Oil for Biodiesel Production

Abstract: The aim of this study was to investigate the potential of the green microalga Chlorella saccharophila as a source of oil for biodiesel production. We evaluated for the first time, the effect of salinity and/or nitrogen depletion (ND) on cell growth, lipid accumulation and lipid profile in this microalga. The fatty acid methyl esters (FAME) identified for C. saccharophila in this study consisted of C-16:0, C-18:0, C-18:1 cis, and C-18:1 trans. Among these, C-18:1 (indicator of biodiesel quality) was the main FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…Several researchers (Herrera-Valencia et al, 2011;Isleten-Hosoglu et al, 2012;Chinnasamy et al, 2010;Tan and Johns, 1991) indicated that higher oil productivities were achieved using the Chlorella saccharophila These values are higher than those obtained in this study. The differences can be attributed to the varying cultivation periods, variation in nutrient systems and the effectiveness in the oil extraction methods used.…”
Section: Effect Of Microalgae Typecontrasting
confidence: 56%
“…Several researchers (Herrera-Valencia et al, 2011;Isleten-Hosoglu et al, 2012;Chinnasamy et al, 2010;Tan and Johns, 1991) indicated that higher oil productivities were achieved using the Chlorella saccharophila These values are higher than those obtained in this study. The differences can be attributed to the varying cultivation periods, variation in nutrient systems and the effectiveness in the oil extraction methods used.…”
Section: Effect Of Microalgae Typecontrasting
confidence: 56%
“…This response allows C. reinhardtii to tolerate certain saline concentrations (up to 200 mM NaCl) [21]. Osmotic stress by NaCl has been shown to increase lipid accumulation in some microalgae, including the marine Dunaliella tertiolecta [34], and the fresh water Botryococcus braunii [27] and Chlorella saccharophila [14]. Recently, it was shown that NaCl stress from 20 to 100 mM NaCl can also induce TAG accumulation in C. reinhardtii [32].…”
Section: Introductionmentioning
confidence: 97%
“…The effectiveness of this type of inducer mainly depends on the use of iron salt, zinc salt, and sodium salt (NaCl, NaHCO 3 , NaAC) etc. (Einicker-Lamas et al, 2002;Herrera-Valencia et al, 2011;Liu et al, 2008;Xia et al, 2013Xia et al, , 2014. However, the effects are not evident in numerous microalgae strains when iron salt and zinc salt are used for induction.…”
Section: Introductionmentioning
confidence: 99%